2020
DOI: 10.21037/tcr.2020.02.16
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the clinical characteristics and radiological features of primary pulmonary lymphoma

Abstract: Background: The retrospective study was mainly performed to determine the clinical symptoms and radiological characteristics of primary pulmonary lymphoma (PPL) to improve the recognition and diagnosis of the disease.Methods: Between June 2007 and June 2019, the clinical data and radiological images of the 16 patients with PPL confirmed by pathology were retrospectively analyzed.Results: Among the 16 patients with PPL (6 males and 10 females, aged 32 to 72 years, with a median age of 55.13 years), 9 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
1
6
1
Order By: Relevance
“…In this study, the average age of MALToma patients was 56.17 years, consistent with previous reports 9,12,13 . The youngest patient was 33 years old; diagnosis at this age has rarely been reported.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the average age of MALToma patients was 56.17 years, consistent with previous reports 9,12,13 . The youngest patient was 33 years old; diagnosis at this age has rarely been reported.…”
Section: Discussionsupporting
confidence: 91%
“…[13,27,28] Even though several studies have endeavored to explore the CT characteristics of PPL, diagnosis of this disease entity remains an intractable conundrum due to its nonspecific and diverse radiological abnormalities. [7,10,29,30] The imaging findings of PPL can be divided into three patterns: single nodular/mass pattern, multiple nodular/mass pattern, and pneumonia-like consolidative pattern. [11] Zhang et al [31] reviewed non-contrast enhanced CT in 62 PPL patients and revealed that the most frequent findings of PPL are consolidations, followed by nodules and masses.…”
Section: Discussionmentioning
confidence: 99%
“…As lung cancer patients exhibited severe respiratory symptoms, irregularly thickened bronchial wall, narrow or interrupted bronchial lumen, increased in lung cancer-related tumor markers such as CEA and SCC, and usually a higher FDG uptake. In case of peripheral lung cancer, the fine burr, pleural depression, vascular aggregation and other signs in the edge were well known ( 8 , 42 ). In lobar pneumonia, lamellar consolidation shadows were evident, the bronchial wall was usually not thickened, the bronchial lumen occured as relatively unobtruded, and hilar and mediastinal lymph nodes generally were not enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary tuberculosis was found to be located mainly in the apicoposterior segment of the upper lobe and the dorsal segment of the lower lobe with satellite foci around the lesion. Both calcification and necrosis were also seen in some lesions, and the tuberculin test was positive ( 8 , 42 , 44 ). Nevertheless, PPL patients often had periodic fever, mild symptoms, air bronchial signs were common in the lesions, bronchial lumen was unobstructed, and the bronchial wall was uniformly thickened in the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation